All quiet on the eastern front? Disruption scenarios of Russian natural gas supply to Europe. (May 2015) - Richter, Philipp M.; Holz, Franziska
Abstract: The 2014 Russian–Ukrainian crisis reignited European concerns about natural gas supply security recalling the experiences of 2006 and 2009. However, the European supply situation, regulation and infrastructure have changed, with better diversified import sources, EU member states being better connected and a common regulation on the security of supply has been introduced. Nevertheless, European dependency on natural gas remained high. This paper investigates different Russian natural gas export disruptions scenarios and analyses short- and long-term reactions in Europe. We use the Global Gas Model (GGM), a large-scale mixed complementarity representation of the natural gas sector with a high level of technical granularity with respect to storage and transportation infrastructure. While we find that most of the EU member states are not severely affected by Russian disruptions, some East European countries are very vulnerable. Prioritizing the removal of infrastructure bottlenecks is critical for securing a sufficient natural gas supply to all EU member states. Highlights: We analyze disruption scenarios of Russian natural gas exports to Europe. Most EU countries are only weakly affected by a complete Russian supply disruption. We find that Eastern Europe is vulnerable to Russian supply disruptions. We identify infrastructure bottlenecks in the European natural gas network. We find that the large EU LNG import capacity is not sufficiently connected.